The interplay of social identity and norm psychology in the evolution of human groups. (13th March 2023) - Kish Bar-On, Kati; Lamm, Ehud
Abstract : People's attitudes towards social norms play a crucial role in understanding group behaviour. Norm psychology accounts focus on processes of norm internalization that influence people's norm-following attitudes but pay considerably less attention to social identity and group identification processes. Social identity theory in contrast studies group identity but works with a relatively thin and instrumental notion of social norms. We argue that to best understand both sets of phenomena, it is important to integrate the insights of both approaches. Social status, social identity and social norms are considered separate phenomena in evolutionary accounts. We discuss assumptions and views that support this separation, and suggest an integrated view of our own. We argue that we should be open to the early origins of human social complexity, and conjecture that the longer that the human social world involved multi-level societies the more probable it is that norm psychology and social identity interacted in rich ways. This article is part of the theme issue 'Human socio-cultural evolution in light of evolutionary transitions'.